Peranan Etika Bisnis Dalam Membangun Budaya Kerja Yang Sehat di Pt Link Net Tbk - Sulistyo Sulistyo; Aprillia Putri Kusumaningrum; Chicha Adita Maharani; Diky Agus Wiranto; Erlin Rahmawati; Aris Prio Agus Santoso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Business ethics play an important role in creating and maintaining a healthy work culture in a company. PT Link Net Tbk is a company that operates based on the principles of business ethics. This research discusses how the application of business ethics principles can influence a company's internal dynamics. The Research was conducted through direct observation. Research shows that business ethics have become the basis for internal policies, decision-making, and management-employee relations. Researchers took two divisions as samples for comparison, namely the construction division and the marketing division. There are differences between the two divisions in maintaining the work environment. Considering that the marketing division has tighter competition between sales some business ethics are not paid attention to, which causes frequent conflicts in the work environment. The results of this research indicate that ethical business practices are critical to maintaining a fair, inclusive, and productive work environment, which will ultimately support the company's long-term success.